Continuous insulin administration via complex central venous catheter infusion tubing is another risk factor for blood glucose imbalance. A retrospective study - Maury, Eric (Springer, 2012)
BACKGROUND: We assessed the potential impact of infusion tubing on blood glucose imbalance in ICU patients given intensive insulin therapy (IIT). We compared the incidence of blood glucose imbalance in patients equipped, in a nonrandomized fashion, with either conventional tubing or with a multiport infusion device. METHODS: We retrospectively analyzed the nursing files of 35 patients given IIT through the distal line of a double-lumen central venous catheter. A total of 1389 hours of IIT were analyzed for occurrence of hypoglycemic events [defined as arterial blood glucose below 90 mg/dL requiring discontinuation of insulin]. RESULTS: Twenty-one hypoglycemic events were noted (density of incidence 15 for 1000 hours of ITT). In 17 of these 21 events (81%), medication had been administered during the previous hour through the line connected to the distal lumen of the catheter. Conventional tubing use was associated with a higher density of incidence of hypoglycemic events than multiport infusion device use (23 vs. 2 for 1,000 hours of IIT; rate ratio = 11.5; 95% confidence interval, 2.71–48.8; p < 0.001). CONCLUSIONS: The administration of on-demand medication through tubing carrying other medications can lead to the delivery of significant amounts of unscheduled products. Hypoglycaemia observed during IIT could be related to this phenomenon. The use of a multiport infusion device with a limited dead volume could limit hypoglycemia in patients on IIT.